Mid Phanerozoic stromatolites in the Northern Perth Basin: Understanding their evolution and occurrence - Olden, Liam J. (Curtin University, 2020)
Stromatolites from the northern Perth Basin, Western Australia, purported to be associated with the End Permian mass extinction (EPME), were re-examined through several new sites over an expanded 24 km2. New lithological relationships show the stromatolites are intimately associated with a clastic sequence and formed within a fluvio-lacustrine setting. A revised mid to late Permian age is proposed for the stromatolites, disassociated from the EPME. Stromatolite microstructures representing remnant skeletal cyanobacteria are exceptionally preserved throughout.